A neurocognitive model of early onset persistent and desistant antisocial behavior in early adulthood - van de Groep, Ilse H.; Bos, Marieke G. N.; Popma, Arne; Crone, Eveline A.; Jansen, Lucres M. C. (Frontiers in Human Neuroscience, 2023)
It remains unclear which functional and neurobiological mechanisms are associated with persistent and desistant antisocial behavior in early adulthood. We reviewed the empirical literature and propose a neurocognitive social information processing model for early onset persistent and desistant antisocial behavior in early adulthood, focusing on how young adults evaluate, act upon, monitor, and learn about their goals and self traits. Based on the reviewed literature, we propose that persistent antisocial behavior is characterized by domain-general impairments in self-relevant and goal-related information processing, regulation, and learning, which is accompanied by altered activity in fronto-limbic brain areas. We propose that desistant antisocial development is associated Neurocognitive social information processing model of early adult antisocial development 2 Classification: Internal with more effortful information processing, regulation and learning, that possibly balances selfrelevant goals and specific situational characteristics. The proposed framework advances insights by considering individual differences such as psychopathic personality traits, and specific emotional characteristics (e.g. valence of social cues), to further illuminate functional and neural mechanisms underlying heterogenous developmental pathways. Finally, we address important open questions and offer suggestions for future research to improve scientific knowledge on general and contextspecific expression and development of antisocial behavior in early adulthood.